Qualitative realist evaluation of an occupational therapy intervention programme (ABLE), addressing ability to perform activities of daily living among persons with chronic conditions - Vita Hagelskjær; Eva Ejlersen Wæhrens; Cecilie von Bülow; Kristina Tomra Nielsen (BMC Health Services Research, 2024)
Abstract Background Chronic conditions are associated with problems related to performance of activities of daily living (ADL) stressing a need to develop and evaluate intervention programmes addressing such problems. Hence, the ABLE programme was developed, and its feasibility evaluated. Implementing intervention programmes in community-based rehabilitation settings requires understanding of how the programme works in various contexts. Applying a realist evaluation approach, the aim of this study was to identify and evaluate interactions between contexts, mechanisms, and outcomes in the ABLE 2.0, to confirm, refine, or reject aspects of the initial programme theory. Methods Realist evaluation using qualitative data collected in the ABLE 2.0 randomised controlled trial (n = 78). Based on the ABLE 2.0 initial programme theory, qualitative realist interviews were conducted among receivers (n = 8) and deliverers (n = 3) of the ABLE 2.0 in a Danish municipality. Transcripts were coded, and context-mechanism-outcome configurations were extracted and grouped into contiguous themes. Results were then held up against the initial programme theory. Results Four contiguous themes were identified including a total of n = 28 context-mechanism-outcome configurations: building a foundation for the entire intervention; establishing the focus for further intervention; identifying and implementing relevant compensatory solutions; and re-evaluating ADL ability to finalise intervention. Overall, the ABLE 2.0 initial programme theory was confirmed. The evaluation added information on core facilitating mechanisms including active involvement of the client in the problem-solving process, a collaborative working relationship, mutual confidence, and a consultative occupation-based process using compensatory solutions. Several contextual factors were required to activate the desired mechanisms in terms of supportive management, referral procedures encouraging the problem-solving process, delivery in the client’s home, skilled occupational therapists, and clients feeling ready for making changes. Conclusions The ABLE 2.0 represents a coherent problem-solving occupational therapy process, applicable across sex, age, and diagnoses with the potential to enhance ADL ability among persons with chronic conditions, when delivered as part of community-based rehabilitation services. Knowledge about the interactions between contextual factors, mechanisms, and outcomes in the ABLE 2.0 is central in case of future implementation of the programme in community-based rehabilitation settings. Trial registration The trial was prospectively registered on www.ClinicalTrials.gov (registration date: 05/03/2020; identifier: NCT04295837 ) prior to data collection that occurred between August 2020 and October 2021.